Role of SNARE-dependent gliotransmitters release by astrocytes upon Aβ-mediated excitotoxicity - Gomes, Joana Isabel Ferreira da Graça (2021)
Tese de mestrado, Neurociências, Universidade de Lisboa, Faculdade de Medicina, 2020